Coincidence of hand-foot syndrome and diffuse erythema – cutaneous side-effects of sorafenib - Jankowska-Konsur, Alina; Rusin-Tupikowska, Agnieszka; Tupikowski, Krzysztof; Maj, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Hand-foot syndrome (palmoplantar erythrodysesthesia) is a toxic reaction provoked by certain types of chemotherapy or biological therapy. It is characterized by erythema, hyperkeratosis and bullae occurring mainly on the palms and soles. In patients treated with sorafenib, a tyrosin kinase inhibitor with antiangiogenic and antiproliferative activity, hand-foot syndrome is one of the most common side-effects. Rarely, an association of hand-foot syndrome and diffuse erythema is observed. Objective. Presentation of clinical picture of sorafenib induced skin side effects. Case report. We present a 71-year-old patient treated with sorafenib for disseminated renal cancer with hand-foot syndrome and diffuse erythema, which appeared six days after sorafenib administration. The patient was treated with systemic and topical steroids, antihistamins, and topical creams with urea. In addition, the sorafenib dose was reduced by half and the skin condition improved. Conclusions. Novel anticancer therapies are characterized by high toxic potential against the skin, what creates a big challenge not only for oncologists but also for dermatologists.